Agricultural input subsidies : the recent Malawi experience - Chirwa, Ephraim W.; Dorward, A. (Andrew). (Oxford : Oxford University Press, 2013)
This title provides a detailed, comprehensive, and objective analysi s of Malawi's agricultural input subsidy programme, its history, implem entation, achievements, and shortcomings.
Includes bibliographical references (pages 273-288) and indexes.
Keywords: Agricultural subsidies -- Malawi; Economic development -- Malawi; Agricultural subsidies -- Developing countries; Economic development -- Developing countries